MANAJEMEN PESERTA DIDIK DALAM MANAJEMEN BERBASIS SEKOLAH DI SD TARSISIUS VIRETA - Almanisa Nur Fadilla; Denisa Ramadhani; Regina Permata Dewi (CV Putra Publisher, 2022)
Student management aims to standardize various activities in the field of student affairs, so that learning activities in schools can be carried out smoothly, and in an orderly manner. To achieve this goal, the three main tasks in the field of student management are student admissions, learning progress activities, and subject guidance and development. The author uses qualitative research methods based on literature studies concerning books, journals, scientific articles, etc. This research is also equipped with an interview method in deepening the content of the discussion and as a complement to the content of the discussion. Student Management as management has the most important role in all matters relating to its relation to students starting from the existence of a plan, acceptance of new students, coaching in the form of activities that exist for students while in school until come to students who have completed their educational studies at school. Determination of the number of students accepted by SD Tarsisius Vireta in one class containing 28 students per class. Each class at SD Tarsisius Vireta has 5 classes, namely from A - E. However, for example, if there are 28 students in each class and A - E has been filled but there are still 2 more students then the 2 students will not be accepted by the party. school. We can conclude that the management at SD Tarsisius Vireta is very good and very well organized.